Calculation of the Vertical Velocity in the Asian Summer Monsoon Anticyclone Region Using the Thermodynamic Method With in situ and Satellite Data - Guo, Dong; Shen, Peijie; Shi, Chunhua; Wang, Meirong; Liu, Yu; Zhang, Chenxin; Li, Wenwen (Frontiers in Earth Science, 2020)
Correctly calculating the vertical velocity of the Asian summer monsoon anticyclone (ASMA) region is helpful for accurately knowing the ozone stratosphere–troposphere exchange, so as to explore the variation of ozone in the ASMA region. Therefore, the vertical velocity over the ASMA in June, July, August, and September 2012 and 2016 was calculated using the thermodynamic method, which may avoid the deviations produced by the kinematics method using the mass continuity equation. In order to improve the accuracy, we used high-resolution heating rate datasets obtained via the radiation model in Canadian Atmospheric Global Climate Model called CanAM4.3_RAD based on in situ observations and revised satellite data from MLS/AIRS. The vertical velocity calculated by the thermodynamic method (VT) is then compared with the data from ERA-Interim (VERA–I). In the daytime, values of VT were similar to VERA–I and were dominated by ascending motion, although VT showed descending motion at the western edge of the ASMA below 100 hPa. The intensity of VT was slightly smaller than that of VERA–I at lower levels (200–100 hPa) over the ASMA region and significantly weaker above 100 hPa. The situation was more complex at night. Both VT and VERA–I showed the convergence of vertical wind at 150 hPa and the divergence at 80 hPa, but VT had a smaller standard deviation. VT showed descending in the western and northern ASMA, but VERA–I only descended in the west. The descending motion in the west, seen in both VT and VERA–I, is produced by the heating difference between the Qinghai–Tibet Plateau and the Iranian Plateau. The difference of the two vertical velocities in the northern ASMA may indicate the different understandings of the local Hadley Circulation and local Brewer-Dobson Circulation.